2-(3-Fluorophenyl)-3-methylsulfanyl-5-phenyl-1-benzofuran - Seo, Pil Ja (International Union of Crystallography, 2011)
In the title compound, C(21)H(15)FOS, the dihedral angles between the mean plane of the benzofuran fragment and the pendant 3-fluorophenyl and phenyl rings are 1.76 (5) and 32.29 (5)°, respectively. In the crystal, molecules are linked by a slipped π–π interaction between the furan and benzene rings of neighbouring molecules [centroid–centroid distance = 3.665 (2) Å, interplanar distance = 3.391 (2) Å and slippage = 1.390 (2) Å].